2018
DOI: 10.1155/2018/2856518
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Inflammatory Reactions by Low-Dose Ionizing Radiation: Cytokine Release of Murine Endothelial Cells Is Dependent on Culture Conditions

Abstract: Background In many European countries, patients with a variety of chronical inflammatory diseases are treated with low-dose radiotherapy (LD-RT). In contrast to high-dose irradiation given to tumor patients, little is known about radiobiological mechanisms underlying this clinical successful LD-RT application. The objective of this study was to gain a better insight into the modulation of inflammatory reactions after LD-RT on the basis of endothelial cells (EC) as major participants and regulators of inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…In our earlier studies, we compared the binding of monocytes to three different EC lines (H5V, mlEND1, and bEND3). It has been clearly observed that not only a change in the inflammatory cytokine release but also adhesion capacity like that of monocyte binding to ECs depended on the origin of the ECs [35]. The dependence of IR response on the origin of ECs was also described by Nicolson and his coworkers [21].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In our earlier studies, we compared the binding of monocytes to three different EC lines (H5V, mlEND1, and bEND3). It has been clearly observed that not only a change in the inflammatory cytokine release but also adhesion capacity like that of monocyte binding to ECs depended on the origin of the ECs [35]. The dependence of IR response on the origin of ECs was also described by Nicolson and his coworkers [21].…”
Section: Discussionmentioning
confidence: 90%
“…It has also been stated that microvascular endothelial cells from human lungs (HLEC) can secrete chemokines like MCP-1 or IL-8 generally and in higher concentrations after TNF- α stimulation [53]. In our former study in murine EC mlEND.1, the concentration of MCP-1 48 hours after IR with 0.1 Gy was 10-fold (2D) or 5.4-fold (3D) higher in activated cells compared to the nonactivated cells [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite the strong data supporting the use of more physiologically relevant tissue models in radiobiological studies, to date their application to investigate in vitro the effect of ionizing radiation on the microvasculature is scarce. The secretion of inflammatory markers was found to differ significantly for endothelial cells cultured in standard 2D plastic well‐plates and on nonadherent surfaces promoting 3D clustering . On the other hand, the kinetics of p53 binding protein 1 linked to DNA double‐strand breaks were similar for human umbilical vein endothelial cells (HUVECs) cultured either in 2D or within tube‐like vascular structures …”
Section: Introductionmentioning
confidence: 99%